PENGARUH KOMPRES LIDAH BUAYA (ALOE VERA) TERHADAP PENURUNAN NYERI PEMBENGKAKAN PAYUDARA IBU MENYUSUI HARI 1-3 DI KLINIK CITRA MARINDA KECAMATAN DELITUA KAB. DELI SERDANG TAHUN 2023 - Sitepu, Stefani Anastasia; Natalia, Kristin; Hutabarat, Vitilina (JURNAL ILMIAH DHDT - KEBIDANAN, 2024)
Breast swelling is a breastfeeding trouble that mothers regularly revel in after giving start. Breast swelling can cause pain that influences the breastfeeding process. This look at aims to determine the impact of applying aloe vera poultices on lowering pain related to breast swelling in postpartum girls at Citra Marindal medical institution, District. Delitua Regency Deli Serdang, 2023. The sort of studies used is quantitative research with a quasi-experimental design with a pretest-posttest institution approach. The sample for this observe became all postpartum mothers with as much as sixteen stories the usage of the whole sampling method on the Citra Marindal clinic. The evaluation used is the Wilcoxon check. The outcomes of a non-parametric statistical test, the Wilcoxon check, confirmed that p-fee = <.half; which means applying aloe vera compresses reduces the pain due to breast swelling in postpartum girls. pointers for moms after childbirth to know about aloe vera compresses can lessen the pain because of swelling with advice from health professionals.